Membrane-associated glucose-methanol-choline oxidoreductase family enzymes PhcC and PhcD are essential for enantioselective catabolism of dehydrodiconiferyl alcohol - Takahashi, Kenji (American Society for Microbiology, 2015)
Sphingobium sp. strain SYK-6 is able to degrade various lignin-derived biaryls, including a phenylcoumaran-type compound, dehydrodiconiferyl alcohol (DCA). In SYK-6 cells, the alcohol group of the B-ring side chain of DCA is initially oxidized to the carboxyl group to generate 3-(2-(4-hydroxy-3-methoxyphenyl)-3-(hydroxymethyl)-7-methoxy-2,3-dihydrobenzofuran-5-yl) acrylic acid (DCA-C). Next, the alcohol group of the A-ring side chain of DCA-C is oxidized to the carboxyl group, and then the resulting metabolite is catabolized through vanillin and 5-formylferulate. In this study, the genes involved in the conversion of DCA-C were identified and characterized. The DCA-C oxidation activities in SYK-6 were enhanced in the presence of flavin adenine dinucleotide and an artificial electron acceptor and were induced ca. 1.6-fold when the cells were grown with DCA. Based on these observations, SLG_09480 (phcC) and SLG_09500 (phcD), encoding glucose-methanol-choline oxidoreductase family proteins, were presumed to encode DCA-C oxidases. Analyses of phcC and phcD mutants indicated that PhcC and PhcD are essential for the conversion of (+)-DCA-C and (-)-DCA-C, respectively. When phcC and phcD were expressed in SYK-6 and Escherichia coli, the gene products were mainly observed in their membrane fractions. The membrane fractions of E. coli that expressed phcC and phcD catalyzed the specific conversion of DCA-C into the corresponding carboxyl derivatives. In the oxidation of DCA-C, PhcC and PhcD effectively utilized ubiquinone derivatives as electron acceptors. Furthermore, the transcription of a putative cytochrome c gene was significantly induced in SYK-6 grown with DCA. The DCA-C oxidation catalyzed by membrane- associated PhcC and PhcD appears to be coupled to the respiratory chain.